Patient-reported Outcome Measures for Peripheral Nerve Injuries: A Systematic Review - Chloe R. Wong, MD; Marta Karpinski, MSc; Kristen M. Davidge, MD, MSc, FRCS(C); Anne Klassen, PhD; Jana Dengler, MD, MASc, MHSc, FRCS(C) (Plastic and Reconstructive Surgery, Global Open)
Background:. The goal of managing patients with peripheral nerve injuries is to improve how a patient feels and functions. This goal is best assessed with patient-reported outcome measures (PROMs), which elicit patient concerns, treatment goals, and clinical progression. This study reviews existing PROMs for adult patients with peripheral nerve injuries to assess how comprehensively they measure outcomes important to patients. Methods:. A systematic review of Ovid MEDLINE, Scopus, Web of Science, and Embase (from inception to August 13, 2022) was conducted to identify PROMs developed for adult patients with peripheral nerve injuries. Studies were included if (1) the study population involved traumatic or acquired peripheral nerve injuries; (2) they were randomized controlled trials, cohort studies, or single-arm observational studies; (3) participants were 18 years or older; and (4) PROMs were used to assess quality of life or patient satisfaction. Results:. A total of 378 studies were included in this systematic review. We identified 141 unique PROMs used in the adult peripheral nerve injury literature: 20 are disease-specific (14%), 10 are function-specific (7%), 19 are mental health and well-being–specific (13%), 11 are quality of life–specific (8%), 32 are body region–specific (23%), 29 are symptom-specific (21%), 3 are satisfaction-specific (2%), 15 are generic (11%), and 2 are other (1%). Conclusions:. There exists considerable heterogeneity of PROMs used in research on patients with peripheral nerve injuries. None of the PROMs comprehensively assess this patient population. The need for the development of a comprehensive PROM for this patient population is highlighted.